Social dominance orientation, right‐wing authoritarianism, and political attitudes toward governmental performance during the COVID‐19 pandemic. Issue 1 (25th January 2022) - Zhai, Yida; Chong, Li Ying; Liu, Yunzhe; Yang, Shuting; Song, Changfa
Abstract: This research examined the association of social dominance orientation (SDO) and right‐wing authoritarianism (RWA) with the evaluations of the government's anti‐coronavirus disease 2019 (COVID‐19) policies and performance. In Study 1 ( N = 261), we found that SDO and RWA were positively associated with resistance to criticism about the government's anti‐COVID‐19 measures. In addition, SDO was positively associated with favorable evaluations of the government's performance in handling the crisis. Support for lockdown policies mediated these attitudes. In Study 2 ( N = 438), the results show that SDO and RWA had indirect associations with beliefs in the superiority of China's political system through three mediation variables. Evaluations of the US government's performance in handling the COVID‐19 pandemic were negatively associated with beliefs in the superiority of China's political system, and there was a negative relationship between evaluations of the Chinese and US governments' performances.